Avaliação de superelasticidade e deformação das molas fechadas de níquel-titânio sob diferentes ativações - Vieira, Camilla Ivini Viana [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Avaliar se molas fechadas de níquel-titânio de diferentes marcas comerciais Morelli®, Orthometric®, Ormco®, GAC® apresentam comportamento superelástico (SE), se o plateau de força produzido condiz com o fornecido pelo fabricante e determinar quais são os percentuais de deformação das molas testadas. Materiais e Métodos: Dois artigos científicos foram redigidos e utilizados para a avaliação dos propósitos apresentados e para compilação de um pequeno guia clínico. Resultados: A maioria das molas mostrou-se superelásticas a partir da ativação inicial de 400%, apenas um subgrupo não apresentou comportamento superelástico em nenhuma das ativações. Os plateaus SE fornecidos pelos fabricantes do grupo 1 e subgrupo 3C não correspondem aos encontrados nesse estudo. Para os subgrupos 3A, 4E e 4A as molas apresentaram o plateau correspondente com o fabricante a 600%, 500% e a 400% de ativação inicial, respectivamente. Nos subgrupos 2A, 2B, 4B, 4C, 4D, 4F e 4G os plateaus SE corresponderam aos valores fornecidos pelo fabricante de 600 a 800%, 400 a 500%, 600 a 800%, 400 a 700%, 400 a 600%, 400 a 600% e de 500 a 700% de ativação inicial. A deformação das molas do subgrupo 1A e 1B não foram diferentes de 400 a 700% e 400 a 800% de ativação respectivamente. A deformação das molas do subgrupo 2A e 2B foram iguais de 400 a 700% e 400% a 600% de ativação 20 respectivamente. As deformações causadas de 400 a 700% de ativação no subgrupo 3A foram iguais. No subgrupo 3C, as deformações ocorridas em 600% e 700% de ativação foram iguais. No subgrupo 4A, as deformações ocorridas de 400 a 800% de ativação foram iguais. No subgrupo 4B, 4D, 4C e 4E, todas as deformações foram iguais. No subgrupo 4G as deformações foram iguais de 500 a 800%. Conclusões: A maioria das molas mostrou-se SE a partir da ativação inicial de 400%...

To verify whether different nickel-titanium closed coil springs Morelli®, Orthometric®, Ormco®, GAC® have superelastic (SE) behavior, if the force plateaus are consistent with the information provided by the manufacturer and to determine the percentage of deformation according to initial activation. Materials and Methods: Two scientific papers were compiled for evaluation. Results: Most of the subgroups showed SE behavior when activated 400% and one subgroup was not SE. The plateaus SE provided by manufacturers of a group and subgroup 3C do not correspond to those found in this study. For the subgroups 3A,4A and 4E springs showed a plateau corresponding to the manufacturer with 600%, 500% and 400% of initial activation, respectively. In subgroups 2A, 2B, 4B, 4C, 4D, 4F and 4G plateaus corresponded to the values provided by the manufacturer from 600 to 800%, 400 to 500%, 600 to 800%, 400 to 700%, 400 to 600 %, 400 to 600 and from 500% to 700% of initial activation. The subgroups behaved differently when it comes to deformation: the deformations of subgroup 1A and 1B were the same: from 400 to 700% and from 400 to 800% activation, respectively. The deformations on subgroups 2A and 2B were the same: from 400 to 700% and from 400 to 600% of activation, 23 respectively. The deformations on subgroup 3A were the same from 400 to 700% of activation, while in subgroup 3C, the deformations were the same from 600 to 700% of activation. In subgroup 4A, the deformations were the same from 400 to 800% activation. In the subgroups 4B, 4D, 4C and 4E, deformations were equal on all activations, while on subgroup 4G deformations were similar from 500 to 800%. Conclusions: Most of the springs were SE from 400% of activation on. In most subgroups, the deformations, up to 700% of initial activation, were the same. The force plateaus were inversely proportional on initial activation
Keywords: Molas fechadas; Molas - Comportamento superelástico; Orthodontics; Closed coil - Superelastic behavior